Course and Outcome of Early European Lyme Neuroborreliosis (Bannwarth Syndrome): Clinical and Laboratory Findings. (8th May 2016) - Ogrinc, Katarina; Lusa, Lara; Lotrič-Furlan, Stanka; Bogovič, Petra; Stupica, Daša; Cerar, Tjaša; Ružić-Sabljić, Eva; Strle, Franc
Abstract : Our patients with Bannwarth syndrome had fewer pretreatment neurological complications than reported decades ago, probably due to earlier recognition and prompt antibiotic treatment. Unfavorable outcome was rare and was predicted by the presence of symptoms 14 days after enrollment. Abstract : Background. Information on the course and outcome of early European Lyme neuroborreliosis is limited. Methods. The study comprised 77 patients (38 males, 39 females; median age, 58 years) diagnosed with painful meningoradiculitis (Bannwarth syndrome) who were followed up for 1 year at a single center. Results. Duration of neurological symptoms before diagnosis was 30 (interquartile range, 14–50) days. The most frequent symptoms/signs were radicular pain (100%), sleep disturbances (75.3%), erythema migrans (59.7%), headache (46.8%), fatigue (44.2%), malaise (39%), paresthesias (32.5%), peripheral facial palsy (PFP) (36.4%), meningeal signs (19.5%), and pareses (7.8%). Cerebrospinal fluid (CSF) analysis revealed lymphocytic/monocytic pleocytosis, elevated protein concentration, and intrathecal synthesis of borrelial immunoglobulin M and immunoglobulin G antibody in 100%, 81.1%, 63%, and 88.7% of patients, respectively. Borreliae (predominantly Borrelia garinii ) were isolated from CSF, skin, and blood in 15.6%, 40.6%, and 2.7% of patients, respectively. The outcome after 14-day treatment with ceftriaxone was favorable in 87.8% of patients. Control CSF examination at 3 months showed decreased leukocyte counts in all patients; however, 23.3% still had pleocytosis (>10 × 10 6 cells/L). A model based on pretreatment data and the findings at the end of 14-day antibiotic treatment accurately predicted which patients would have an unfavorable outcome 6 or 12 months after treatment. Conclusions. Our patients had fewer pretreatment neurological complications (PFP, pareses) than reported for Bannwarth syndrome decades ago, probably as the result of earlier recognition and prompt antibiotic treatment. Unfavorable outcome was rare and was predicted by the continued presence of symptoms 14 days after commencement of treatment.